Methanol to dimethyl ether pilot fuel synthesis system and modeling for marine engine applications - Gilbert, Alayna, author; Windom, Bret, advisor; Montgomery, Dave, committee member; Piffarerio, Minnie, committee member (Colorado State University. Libraries, 2026)
The marine shipping industry is reliant on compression engines powered by heavy liquid petroleum-based fuels and is thus responsible for 3% of global greenhouse gas emissions [1]. Marine shipping emissions must be reduced by using energy dense, space-efficient solutions that build off existing infrastructure for timely and economic solutions. This makes de-carbonized alternative fuels such as methanol an excellent approach to reducing maritime emissions. However, the cetane number of methanol is too low to start combusting in a compression engine without pilot fuel. This work focuses on creating an onboard pilot fuel production system that dehydrates methanol to produce dimethyl ether (DME). This dehydration reaction will allow marine ships to bunker and run methanol as the primary fuel while piloting with DME. A test system designed to produce 1/45th of the DME flow rate needed to run a 3512E Marine Auxiliary CAT Engine was used to isolate scale up challenges. The system informed a validated Aspen Plus model that will aid in further scale-up and testing. The experimental system was assessed for methanol conversion rate and DME purity capabilities with reactor temperatures of 150 – 300°C, methanol mass flow rates of 25 – 75 g/min, and system back pressures of 0 – 3 bar. A maximum methanol conversion rate of 70% was achieved at reactor temperatures between 295 – 300°C, a methanol mass flow rate of 25 g/min, and system back pressures of 0 – 1.4 bar. Kinetics calculated from experimental testing were used to develop an Aspen Plus model of the system. The model was then validated against experimental data to verify its predictability of methanol conversion rate and DME purity.
Keywords: modeling; methanol; pilot fuels